Unraveling Determinants of FDI: Insights from Oil-Abundant Economies - Rizky Altsary; Maal Naylah (Economics Development Analysis Journal, 2025)
The significance of natural resources in shaping foreign direct investment (FDI) dynamics cannot be overstated. In oil-abundant countries, these resources act as catalysts and magnets for investment inflows. Against this backdrop, this research aims to dissect the determinants of FDI within oil-rich nations, focusing on four critical factors: natural resources, exchange rates, openness to trade, and market size. The study seeks to unravel the intricate interplay between resource endowments and investment attractiveness by leveraging panel data from six oil-abundant countries (the United States, China, Russia, Canada, Saudi Arabia, and the UAE) over nine years (2011–2019) and employing the fixed effect model as a robust methodology. The results reveal that all factors: natural resources, openness to trade, and market size are statistically significant in affecting FDI inflows. Due to the robust economic conditions in the countries studied exchange rate fluctuations have a limited impact on FDI. Instead, investors prioritize microeconomic factors such as labor wages, logistics costs, and telecommunication tariffs when evaluating business efficiency in investment destinations. Thus, this research provides actionable insights for policymakers to enhance the market environment for local producers, support trade through subsidies and incentives, and focus on resource exploration to attract foreign investors and stimulate economic growth.